RUBBER PLANTATION IN POVERTY ALLEVIATION IN CENTRAL KALIMANTAN PROVINCE: TARGET OF SDGS POINT 1 - Feby Adila Indria Sutrisno; Alexandra Hukom; Dicky Perwira Ompusunggu (SEAN Institute, 2023)
Central Kalimantan Province is the second-largest rubber producer in Indonesia in terms of its contribution to national rubber production. Central Kalimantan rubber production and other domestic production are expected to contribute to poverty and sustainable development goals. The purpose of this research is to determine the impact of land area, rubber production, and GDP on poverty in Central Kalimantan Province. The research method used is panel fixed effect analysis using secondary data, namely statistical data in Central Kalimantan. The results of the variable area of oil palm land in Central Kalimantan Province have a small but significant impact on poverty in the province. With a probability value, the amount of rubber production has a negative but not significant effect on the poverty level. So if the amount of rubber production is high, it can reduce the level of poverty. The GRDP variable has a probability value of 0.2%. Production results and GRDP have a negative relationship, which means that the poverty rate in Central Kalimantan will decrease if palm oil production results and GRDP increase.